2005
DOI: 10.1002/hed.20247
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin—physiology and applications in head and neck disorders

Abstract: This article is structured around a literature review that was carried out using Ovid and Medline with the key words "botulinum," "toxin," and "ENT." Botulinum toxin has been used safely in humans for more than 20 years. The effects are transient, such that treatments are required to be repeated at intervals. Its application to ENT provides a useful tool to treat dystonia, autonomic dysfunction, facial nerve paresis, and hyperfunctional lines. It may also be of benefit in laryngeal rebalancing and the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 96 publications
(95 reference statements)
0
11
1
4
Order By: Relevance
“…However, Lee et al [12] reported a statistically signiWcant decrease in self-assessment pain with the injection of botulinum toxin type A, but at the end of the study patients showed only partial improvement. Some disadvantages of this therapy are: as in other applications, patients experience relapse of FBS symptoms 4-6 months later; there are some cases of resistance associated with frequent administrations (neutralizing antibody production); there are adverse eVects and it is an expensive continuous therapy [5,12,15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, Lee et al [12] reported a statistically signiWcant decrease in self-assessment pain with the injection of botulinum toxin type A, but at the end of the study patients showed only partial improvement. Some disadvantages of this therapy are: as in other applications, patients experience relapse of FBS symptoms 4-6 months later; there are some cases of resistance associated with frequent administrations (neutralizing antibody production); there are adverse eVects and it is an expensive continuous therapy [5,12,15].…”
Section: Discussionmentioning
confidence: 98%
“…The most recent treatment proposed for FBS is the use of botulinum toxin as a blocker of the presynaptic release of acetylcholine, paralyzing the myoepithelial cells, thus inhibiting the supramaximal contraction and improving the pain [5,12,15]. The fact that the botulinum toxin is used with success in other otorhinolaryngology diseases (i.e., spasmodic dysphonia, Frey's syndrome), as a simple, safe and low morbidity procedure, leads some authors to believe and defend that this should be the main therapeutic option in FBS [5].…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum toxin type A acts at the neuromuscular junction by blocking vesicle transport of acetylcholine, and in essence, this produces a chemical denervation (13, 14). It has been used safely and effectively to control the symptoms of patients with disorders of a neural origin and voice disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum toxin type A (Botox®, Allergan, Irvine, CA, USA) is known to be a potent neurotoxin that produces flaccid paralysis of the striated muscle for a period of 2 to 6 months; it has been safely used in humans in the clinical field for more than 20 yr. Its application to the ENT field provides a useful tool to treat spasmodic dysphonia, autonomic dysfunction, Frey syndrome, hemifacial spasm or synkinesis, and hyperfunctional lines (13, 14). Gassner and Sherris (15) reported that the chemoimmobilization of facial wounds with Botox improved the cosmetic appearance.…”
Section: Introductionmentioning
confidence: 99%
“…1 The author reviewed the physiologic features and clinical applications of botulinum toxin in the head and neck area. Although the author evaluated many previous studies, one of the new and important applications of the botulinum toxin, allergic rhinitis, was not included.…”
mentioning
confidence: 99%